Problem solving ability and belief in prospective mathematics teachers - Hidayah, Nurina; Waluya, St. Budi; Walid (AIP conference proceedings, 2022)
Mastery of mathematical problem-solving in prospective teachers is essential to be able to teach to students. In addition, it is supported by the belief that problem-solving, which is constantly changing in each person, affects the problem-solving process—this study, solving mathematical problems in terms of problem-solving beliefs for prospective mathematics teachers. Subject selection criteria are based on problem-solving beliefs divided into the 1st type of belief, the 2nd type of belief, and the 3rd type of belief. Furthermore, the subject of each type of belief worked on the problem-solving questions given online. The results of the analysis of the subject's work show that every kind of belief has been able to fulfill every mathematical problem-solving process, namely 1) holistic understanding of the problem; 2) identify method(s) for a solution; 3) apply the method(s) for solutions; 4) check the accuracy of the solution. The suggestions given need a further understanding that it is essential in every problem-solving process, especially in checking the accuracy so that the same mistakes are not repeated.